The Role of Natural CQDs as Nicotine Detoxification Agents in Oral Mucosa. A Conceptual - Putri, Citra Feriana; Nasution, Abdillah Imron; Afrina, Afrina; Gani, Basri A (Journal of Syiah Kuala Dentistry Society, 2024)
Nicotine, a major component in tobacco products, has adverse effects on the oral mucosa, including an increased risk of oral cancer and periodontal disease. Natural Carbon Quantum Dots (CQDs), carbon nanoparticles less than 10 nm in size, offer potential as nicotine detoxifying agents on the oral mucosa. The unique properties of CQDs, such as large surface area, surface functionalization ability, high biocompatibility, and antioxidant activity, allow them to bind to nicotine, reduce oxidative stress, and modulate inflammatory responses. Thus, CQDs can prevent nicotine attachment to the oral mucosa and reduce tissue damage. However, more research is needed to confirm the effectiveness and safety of natural CQDs in clinical applications as nicotine detoxification agents.